Sosialiasi Literasi Gender Bagi Pemuda-Pemudi Karang Taruna Kelurahan Cawang, Jakarta Timur - Formas Juitan Lase; Mita Yesyca (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2020)
Gender-based injustice and violence can be found around us, but they are often ignored. Meanwhile, gender equality—where men and women have the same appreciation and opportunity they need for self-development in various fields—is a sign of welfare society. Through this community service, the writers along with the students, want to see an increase in gender awareness which become a precondition of welfare society. With a community who are gender literate, there is a hope that gender equality will be able to be realised. Young men and women of the youth organisation in Cawang Village, East Jakarta, are chosen to start this community service. The result showed that almost all participants do not aware of gender-based injustice practices, although they have ever seen or even experienced it around them. Socialisation further is required so that participants not only know, but also understand and able to apply their knowledge in their family and surround environment.